2017
DOI: 10.1186/s12865-017-0220-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of IL-9 producing T cells in the PBMCs of allergic asthmatic patients

Abstract: BackgroundInterleukin-9 (IL-9) was reported as an active participant in the pathogenesis of allergic asthma. This study aimed to investigate the major source ofIL-9 and its effect on interferon γ (IFN-γ) and immunoglobulin (Ig) secretion by B cells.MethodsWe isolated peripheral blood mononuclear cells from children with allergic asthma and healthy children. IL-9, IL-4 and IFN-γ expression were detected by ELISA, ELISpot and Flowcytometry. Expression of transcription factor PU.1 was measured by Western Blot. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Numerous studies, conducted both in humans and mice, recognized the role of IL‐9 and Th9 cells in airway allergic diseases, due to their contribution to airway inflammation. Research on human cohort material revealed an increased IL‐9 expression in bronchoalveolar lavage (BAL) from atopic asthma patients, which is in line with findings of increased IL‐9 production by CD4 T cells in peripheral blood mononuclear cells (PBMCs) from adult atopic asthma patients, as well as from atopic infants after allergen‐specific and polyclonal challenge . Importantly, a correlation between the frequencies of these IL‐9 producing cells and serum IgE levels was also observed in these asthma patients .…”
Section: Th9 Cells In Allergic Diseasessupporting
confidence: 76%
See 2 more Smart Citations
“…Numerous studies, conducted both in humans and mice, recognized the role of IL‐9 and Th9 cells in airway allergic diseases, due to their contribution to airway inflammation. Research on human cohort material revealed an increased IL‐9 expression in bronchoalveolar lavage (BAL) from atopic asthma patients, which is in line with findings of increased IL‐9 production by CD4 T cells in peripheral blood mononuclear cells (PBMCs) from adult atopic asthma patients, as well as from atopic infants after allergen‐specific and polyclonal challenge . Importantly, a correlation between the frequencies of these IL‐9 producing cells and serum IgE levels was also observed in these asthma patients .…”
Section: Th9 Cells In Allergic Diseasessupporting
confidence: 76%
“…Research on human cohort material revealed an increased IL-9 expression in bronchoalveolar lavage (BAL) from atopic asthma patients, 32 which is in line with findings of increased IL-9 production by CD4 T cells in peripheral blood mononuclear cells (PBMCs) from adult atopic asthma patients, 33 as well as from atopic infants after allergen-specific and polyclonal challenge. 26,34 Importantly, a correlation between the frequencies of these IL-9 producing cells and serum IgE levels was also observed in these asthma patients. 33 Interestingly, using a mouse asthma model, it was proven that an anti-IL-9 antibody treatment inhibits airway inflammation by reducing the numbers of eosinophils and lymphocytes as well as the levels of type 2 cytokines IL-4 and IL-13 in the lungs.…”
Section: Diseasesmentioning
confidence: 64%
See 1 more Smart Citation
“…Antagonists to IL-5 have been produced for the treatment of severe asthma (58). Patients suffering from asthma have higher levels of IL-9 producing T-cells in their peripheral blood (59). While not targeted in a current treatment, systemically applied neutralizing antibodies reduces infarct (56).…”
Section: Discussionmentioning
confidence: 99%
“…A proinflammatory effect of IL-9 has been widely described in various allergic disorders, including asthma and allergic rhinitis. 30,31 The fact that the IL-9 level strongly correlates with the severity of the patch test reaction 22 suggests that IL-9 similarly promotes an inflammatory reaction in ACD. The proinflammatory role of IL-9 was previously confirmed in rodents, as ear swelling in Il9 −/− mice was less pronounced in a model of CHS caused by 2,4-dinitrofluorobenzene (DNFB) than in WT mice.…”
Section: Discussionmentioning
confidence: 99%